2015
DOI: 10.1039/c4fo01015a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tannic acid–fish scale gelatin hydrolysate hybrid nanoparticles on intestinal barrier function and α-amylase activity

Abstract: Practical application of tannic acid is limited because it readily binds proteins to form insoluble aggregates. In this study, tannic acid was self-assembled with fish scale gelatin hydrolysates (FSGH) to form stable colloidal complex nanoparticles. The nanoparticles prepared from 4 mg ml(-1) tannic acid and 4 mg ml(-1) FSGH had a mean particle size of 260.8 ± 3.6 nm, and showed a positive zeta potential (20.4 ± 0.4 mV). The nanoparticles acted as effective nano-biochelators and free radical scavengers because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…The particles were composed of gelatin enzymatic digests (GED) and tannic acid (TA) ( Figure 1), which are commercially readily available. The high binding affinity between GED and TA favors the formation of colloidal particles [29]. The formation of GED-TA particles is associated with hydrogen bonding between the hydroxyl groups in TA and the hydroxyproline residues in GED [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The particles were composed of gelatin enzymatic digests (GED) and tannic acid (TA) ( Figure 1), which are commercially readily available. The high binding affinity between GED and TA favors the formation of colloidal particles [29]. The formation of GED-TA particles is associated with hydrogen bonding between the hydroxyl groups in TA and the hydroxyproline residues in GED [29].…”
Section: Introductionmentioning
confidence: 99%
“…The high binding affinity between GED and TA favors the formation of colloidal particles [29]. The formation of GED-TA particles is associated with hydrogen bonding between the hydroxyl groups in TA and the hydroxyproline residues in GED [29]. However, the GED-TA particles are noncovalent crosslinking, which could be easily dissociated at the oil-water interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…TA, as shown in Figure 3 , which is mostly distributed in various plants containing vegetables, fruits, oak, grapes, tea leaves, olives, and others, is a biodegradable, naturally existing polyphenolic compound (Wu et al, 2015b ; Shin et al, 2018 ), and it has been affirmed as a safe potential direct food-product additive by the US Food and Drug Administration (Le et al, 2018 ). TA, as a well-known high-molecular-weight polyphenolic compound and hydrolyzable tannin (Shutava et al, 2005 ), has antidiarrheal, convergence, and hemostatic functions (You et al, 2014 ).…”
Section: Structural Features Of Ta Contributing To Self-assemblymentioning
confidence: 99%
“…Moreover, TA has also been revealed to exhibit high biological activities such as antioxidant, antibacterial, antimutagenic, antiviral, and anticarcinogenic properties (Costa et al, 2011 ; Le et al, 2018 ). These characteristics of high bioactivity, extensive sources, low expense, and good biocompatibility make TA widely used in the leather manufacturing, food processing, and medical and biological applications industries (Wu et al, 2015b ; Abouelmagd et al, 2019 ). In particular, its application in biology and medicine has aroused the interest of scientists.…”
Section: Structural Features Of Ta Contributing To Self-assemblymentioning
confidence: 99%
“…We hypothesized that peptides play a significant role in the cruciferin nanoparticle formation. Several studies have reported the nanoparticle formation after protein hydrolysis such as hybrid nanoparticles fabricated with fish scale gelatin hydrolysate 28 and tannic acid, and peptidic nanoparticles prepared with whey hydrolysates 29 . However, the mechanism of particle formation as well as the responsible peptides for the particle formation have not been studied.…”
Section: Introductionmentioning
confidence: 99%